The Effect of Competency Certification on Employee Performance with Competency Testing as a Variable Mediation (Study at PT. X) - Siswanto, Siswanto; Dewi Yustiana; Koen Irianto Uripan; Sutomo, Sutomo; Siti Nur Soleha (SEAN Institute, 2026)
This study aims to analyze the effect of competency certification on employee performance, with competency testing as a mediating variable, at PT. X. The population of this study was 283 operator employees at PT. X, with a sample of 164 employees. The sampling technique used was purposive sampling. The research method used a quantitative approach with Partial Least Squares (PLS) analysis to test the relationship between variables. The results of the study showed the following findings: Competency certification does not have a significant direct effect on employee performance, Competency certification has a positive and significant effect on competency testing, Competency testing has a positive and significant effect on employee performance, Competency testing acts as a significant mediating variable, where competency certification can improve employee performance through competency testing. Overall, this study concludes that although competency certification does not directly affect performance, it becomes effective in improving employee performance when integrated through a rigorous competency testing process.